Transcriptome and metabolome analysis reveals regulatory networks and key genes controlling barley malting quality in responses to drought stress - Hong, Ye (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 The Authors. Published by Elsevier Masson SAS.. All rights reserved.